Regional Polymorphism Assessment of Myanmar ‘Sein Ta Lone’ Mango (Mangifera indica Linn) from Sintgaing Township Based on Microsatellite Markers - Kyaing, May Sandar; May Phyo, Sein Sandar (Horticultural Biotechnology Research, 2019)
This study was conducted to explore the genetic diversity and relationship of Sein Ta Lone mango cultivars among 20 commercial orchards in Sintgaing Township, Mandalay region. Nine microsatellite (SSR) markers were used to detect genetic polymorphism in a range from (3 to 6) alleles with (4.33) alleles per marker in average. Six out of nine microsatellite markers gave the PIC values of greater than (0.5). Among them, SSR36 held the highest PIC values of (0.691) while MiSHRS39 and MN85 possessed the least PIC values of (0.368) and (0.387) respectively. The genetic diversity was expressed as unbiased expected heterozygosity (UHe) value with an average of (0.561). The genetic relationship was revealed by (UPGMA) dendrogram in a range of (0.69 to 1.00). Based on UPGMA cluster analysis, three main clusters were classified among three different locations. This study was intended to help cultivar characterization and conservation for proper germplasm management with the estimation of genetic variation and relationship in the existing population of Sein Ta Lone mangoes in Sintgaing Township by microsatellite markers.